The application of palm oil fly ash in improving a petroleum well cement characteristics - Samsuri, Ariffin (1997)
The paper presents the results of the laboratory studies on G cement characteristics with respect to the free water, fluid loss, strength development and thickening time when palm oil fly ash (POFA) is added to the cement slurry. Laboratory experiments had been carried out by using G-cement slurry with various amount and types of standard petroleum well cement additivies, and various amount of palm oil fly ash. The ASTM-C 114 procedures was used for the chemical analysis and API Spec. 10 procedures under atmospheric and reservoir conditions for the cement characteristics. The results show that less free water and fluid loss, and better strength development and thickening time when palm oil fly ash is added to the cement slurry. From these results, it can be concluded that palm oil fly ash can be used as an additive for petroleum well cement and G-cement characteristics can be improved when palm oil fly ash was added to the cement slurry. Palm oil fly ash is compatible to be used with others standard petroleum well cement additives. Therefore, the total cement material cost can be reduced since palm oil fly ash is a local product. In addition, the petroleum well cement formulation can be improved for better strength, fluid loss and free water content.